Enhancement of synchronous bio-reductions of vanadium (V) and chromium (VI) by mixed anaerobic culture. (November 2018) - Wang, Song; Zhang, Baogang; Diao, Muhe; Shi, Jiaxin; Jiang, Yufeng; Cheng, Yutong; Liu, Hui
Abstract: The co-occurrence of toxic vanadium (V) and chromium (VI) in groundwater receives incremental attention while knowledge on their interactions in biogeochemical processes is limited, with lack of efficient removal means. This study is the first to realize synchronous bio-reductions of V(V) and Cr(VI) with high efficiency by mixed anaerobic culture. After 72-h operation, 97.0 ± 1.0% of V(V) and 99.1 ± 0.7% of Cr(VI) were removed, respectively, with initial concentration of 1 mM for both V(V) and Cr(VI). Cr(VI) bio-reduction took priority while V(V) detoxification was inhibited. V(IV) and Cr(III) were the identified reduction products, both of which could precipitate naturally. Initial Cr(VI) and acetate concentrations as well as pH affected this process significantly. High-throughput 16S rRNA gene sequencing analysis indicated the accumulation of Anaerolineaceae, Spirochaeta and Spirochaetaceae, which could contribute to V(V) and Cr(VI) bio-reductions. The new knowledge obtained in this study will facilitate understanding the biogeochemical fate of co-existing V(V) and Cr(VI) in groundwater and development of bioremediation strategy for their induced combined pollution. Graphical abstract: Image 1 Highlights: Synchronous reductions of V(V) and Cr(VI) by mixed anaerobic culture are realized. Cr(VI) bio-reduction takes priority while V(V) detoxification is inhibited. Naturally precipitated V(IV) and Cr(III) are the identified reduction products. Initial Cr(VI) and acetate concentrations, pH affected this process significantly. Anaerolineaceae, Spirochaeta, Spirochaetaceae contribute to these bio-reductions. Abstract : Synchronous reductions of V(V) to V(IV) and Cr(VI) to Cr(III) by mixed anaerobic culture are realized, with enhanced Cr(VI) and inhibited V(V) removals.